A novel investigation of statins myotoxic mechanism: effect of atorvastatin on respiratory muscles in hypoxic environment. (1st May 2019) - El-Ganainy, Samar O.; El-Mallah, Ahmed; Abdallah, Dina; Khattab, Mahmoud M.; El-Khatib, Aiman S.; Mohy El-Din, Mahmoud M.
Graphical abstract: Highlights: The study examined the myopathic mechanism of statins on isolated rat hemidiaphragm. In hypoxic conditions, atorvastatin induced significant tetanic fade. Coenzyme Q10 co-treatment preserved muscle activity in low oxygen condition. Abstract: Myopathy is a well-known adverse effect of statins, affecting a large sector of statins users. The reported experimental data emphasized on mechanistic study of statin myopathy on large muscles. Clinically, both large muscles and respiratory muscles are reported to be involved in the myotoxic profile of statins. However, the experimental data investigating the myopathic mechanism on respiratory muscles are still lacking. The present work aimed to study the effect of atorvastatin treatment on respiratory muscles using rat isolated hemidiaphragm in normoxic & hypoxic conditions. The contractile activity of isolated hemidiaphragm in rats treated with atorvastatin for 21 days was investigated using nerve stimulated technique. Muscle twitches, train of four and tetanic stimulation was measured in normoxic, hypoxic and reoxygenation conditions. Atorvastatin significantly increased the tetanic fade, a measure of muscle fatigability, in hypoxic conditions. Upon reoxygenation, rat hemidiaphragm regains its normal contractile profile. Co-treatment with coenzyme Q10 showed significant improvement in defective diaphragmatic contractility in hypoxic conditions. This work showed that atorvastatin treatment rapidly deteriorates diaphragmatic activity in low oxygen environment. The mitochondrial respiratory dysfunction is probably the mechanism behind such finding. This was supported by the improvement of muscle contractile activity following CoQ10 co-treatment.